Pengaruh Pemberian Pupuk Bokashi Limbah Ternak Sapi dan CMA (Cendawan Mikoriza Arbuscula) Terhadap Produksi Tanaman Mentimun Jepang (Cucumis sativus L.) - Gulo, Liber Kristiani; Samah, Eri; Dewi, Dora Silvia (JURNAL AGROPLASMA, 2025)
Japanese cucumber (Cucumis sativus L.) is one of the popular horticultural commodities due to its high nutritional value and benefits for health and beauty. However, the continuous use of chemical fertilizers to increase production can lead to environmental degradation and a decline in soil quality. Therefore, sustainable and eco-friendly cultivation innovations are needed, such as the use of organic fertilizers like cattle manure bokashi and biofertilizers such as Arbuscular Mycorrhizal Fungi (AMF). This study aimed to determine the effect of cattle manure bokashi and AMF application on the growth and yield of Japanese cucumber plants. The research was conducted experimentally using a Randomized Complete Block Design (RCBD) with a combination of bokashi and AMF treatments. Observed parameters included stem diameter, number of fruits per sample, fruit weight, and fruit length. The results showed that the application of bokashi and AMF, both individually and in combination, had a highly significant effect on plant yield. The best combination treatment was able to optimally improve both the quality and quantity of Japanese cucumber production. Keywords : bokashi, CMA, japanese cucumber, organic fertilizer, growth, production